Communicating a climate friendly business model - Essebro, Ludvig (2020)
The world has gathered around the idea that sustainable development is possible. At the same time, corporations are in constant development, both economically, but also in power and authority. While the main goal for corporations always has been to generate profit through their operations, corporations can also serve the needs of the public. By aligning with sustainability, corporations can contribute to sustainable development and a better future. As positive side-effect profitability can be increased, and more loyal customers gathered. However, for this to be possible, corporations need to communicate their contribution to sustainable development in a reliable way. Only then, legitimacy can be attained, and the corporation positioned as sustainable in the mind of its stakeholders.